Effect of Whole Wheat Noodles on Biochemical Indexes and Histopathology of Type 2 Diabetic Rats - Li WU; Yuan ZHANG; Chunhong TANG; Huan YOU; Haijun CHANG; Shuai ZHANG (Shipin gongye ke-ji)
Objective: To investigate the effects of whole wheat noodles on biochemical indexes and histopathology of type 2 diabetic (T2DM) rats. Methods: SD rats were fed continuously for 8 weeks and then randomly divided into normal and high-fat groups. The high-fat group was injected intraperitoneally with streptozotocin (STZ) solution at one time to establish a type 2 diabetic rat model. Then, the diabetic rats were intervened with low, medium, and high doses of whole wheat noodles feed for 8 weeks, respectively. The body weights, dietary intake, and drinking volume of the rats were measured regularly. Fasting glucose value was measured by the tail blood sampling method, and the kit was used to measure the blood lipid biochemical indexes and serum oxidative stress levels. Rats were dissected, and liver, kidney, and pancreas tissues were removed to determine the organ indexes. Section staining was performed, followed by biomicroscopic observation of organ histopathological changes. Results: Compared with the model group, whole wheat noodles intervention significantly slowed down the symptoms of weight loss in diabetic rats (P<0.05), reduced dietary and water intake in diabetic rats (P<0.01), and lowered blood glucose values in diabetic rats (P<0.01), with the best effect in the high-dose group, with a reduction of blood glucose values by 44.87%. It also extremely significantly reduced the serum levels of total cholesterol (TC), triglycerides (TG), and low-density lipoprotein (LDL-C) (P<0.01), with reductions of 53.09%, 79.58%, and 45.11%, respectively, in the high-dose group. Additionally, it increased the content of high-density lipoprotein (HDL-C), with a significant increase of 21.83% in the high-dose group (P<0.05). The total antioxidant capacity (T-AOC), superoxide dismutase (SOD) activity, glutathione peroxidase (GSH-Px) activity, and catalase (CAT) activity significantly increased (P<0.05), while the content of malondialdehyde (MDA) extremely significant decreased (P<0.01). Liver and kidney coefficients were extremely significant decreased (P<0.01), by 19.92% and 16.42% in the high-dose group, respectively, and pancreas coefficients showed no significant difference (P>0.05). The phenomenon of inflammatory cell infiltration in hepatocytes improved, homogeneous thickening of glomerular basement membranes and the increase in the stroma of glomerular tethered membranes were ameliorated, and the morphology of islets showed improvement with reduced autolysis phenomenon. Conclusion: Whole wheat noodle has a significant intervention effect on type 2 diabetes mellitus, manifested in slowing down weight loss, lowering blood glucose values, regulating lipid metabolism and oxidative stress levels in the body, eliminating inflammatory edema in the organs, and restoring cellular damage of the organs in several ways.